Loneliness Problem pada Lansia di Panti Jompo Jasa Ibu Jorong Lakung Kenagarian Situjuh Batua - Wiwit Marta Vella; Linda Yarni (Dinasti Research, 2021)
This research is motivated by the results of interviews that researchers conducted with caretakers and elderly caretakers that many elderly people feel anxious and depressed because of a lack of social relationships with other elderly and people around them and also many who cannot communicate properly due to the physical condition of the elderly. The purpose of this study was to describe the Loneliness Problem in the elderly at the Jorong Lakung Kenagarian Sipuh Batua Nursing Home and the causes of the Loneliness Problem in the Elderly at the Jorong Lakung Kenagarian Sipuh Batua Nursing Home. This research is classified as a qualitative research with a descriptive approach. The key informants were five elderly people who were still able to communicate well and fluently and the rest could not communicate properly and fluently, while the supporting informants were two people, namely the caretaker of the orphanage and caregivers. Data was collected through observation and interviews. Data analysis techniques using data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the description of the Loneliness Problem in the elderly at the Jasa Jompo Nursing Home, Jorong Lakung Kenagarian Sipuh Batua, that there are still many elderly people who feel sad, have no hope, lose loved ones, close themselves, contemplate, feel anxious, lack of social relations in general, even the elderly still have the desire to interact with the people around them. Meanwhile, there are three factors that cause Loneliness Problems in the elderly at the Jorong Lakung Kenagarian Sipuh Batua Nursing Home, namely psychological factors (low self-esteem in the elderly, decreased physical condition, decreased sexual function, decreased psychosocial aspects, social decline in society), cultural and situational factors. (changes in the way of life of the elderly, social roles), and spiritual factors.